Assessment of Ruminal Bacterial and Archaeal Community Structure in Yak (Bos grunniens) - Zhou, Zhenming; Fang, Lei; Meng, Qingxiang; Li, Shengli; Chai, Shatuo; Liu, Shujie; Schonewille, Jan Thomas (Frontiers in Microbiology, 2017)
The aim of this study was to determine the microbial community composition in the rumen of yaks under different feeding regimes. Microbial communities were assessed by pyrosequencing bacterial and archaeal 16S ribosomal RNA gene fragments obtained from yaks (Bos grunniens) from Qinghai-Tibetan Plateau, China. Samples were obtained from 14 animals allocated to either pasture grazing (Graze), a grazing and supplementary feeding regime (GSF), or an indoor feeding regime (Feed). The predominant phyla across feeding regimes were Bacteroidetes (51.06%) and Firmicutes (32.73%). At genus level, twenty-five genera were shared across all samples. The relative abundance of Prevotella in the graze and GSF regime group were significantly higher than that in the feed regime group. Meanwhile, the relative abundance of Ruminococcus was lower in the graze group than the feed and GSF regime groups. The most abundant archea phylum was Euryarchaeota, which accounted for 99.67% of the sequences. Ten genera were detected across feeding regimes, seven genera were shared by all samples, and the most abundant was genus Methanobrevibacter (91.60%). The relative abundance of the most detected genera were similar across groups. Our results suggest that the ruminal bacterial community structures differ across yak feeding regimes while the archaeal community structures are largely similar.